Development of an Android-Based Digital Pop-up Book for Molecular Gastronomy Learning in Vocational Schools - Pipit Fitriani; Nur Qudus; Adhi Kusumastuti; Ade Novi Nurul Ihsani (Universitas Negeri Semarang, 2026)
The learning process in Basic Culinary subjects, particularly on Molecular Gastronomy material, is still limited by the use of less interactive learning media, resulting in low student engagement and learning outcomes. This study aimed to develop an Android-based Digital Pop-up Book learning media and to determine its feasibility, practicality, and effectiveness for Grade X Culinary students at SMK Mataram Semarang. The research employed a Research and Development (R&D) approach using the Four-D (4D) model, consisting of Define, Design, Develop, and Disseminate stages. The research subjects included 40 students divided into an experimental class and a control class. Data were collected through expert validation sheets, teacher and student practicality questionnaires, and pre-test and post-test instruments. The findings indicated that the developed learning media was highly feasible based on material and media expert validation, highly practical according to student responses, and effective in improving students' learning outcomes. The experimental class achieved an average N-Gain score of 55.28% (moderate category), while the control class obtained 13.58% (low category). These findings demonstrate that the Android-based Digital Pop-up Book is an effective, practical, and feasible learning medium for enhancing students' understanding of Molecular Gastronomy.